2013
DOI: 10.3390/ijms141224200
|View full text |Cite
|
Sign up to set email alerts
|

Neuritogenic Monoglyceride Derived from the Constituent of a Marine Fish for Activating the PI3K/ERK/CREB Signalling Pathways in PC12 Cells

Abstract: A neuritogenic monoglyceride, 1-O-(myristoyl) glycerol (MG), was isolated from the head of Ilisha elongate using a PC12 cell bioassay system, and its chemical structure was elucidated using spectroscopic methods. MG significantly induced 42% of the neurite outgrowth of PC12 cells at a concentration of 10 μM. To study the structure-activity relationships of MG, a series of monoglycerides was designed and synthesised. Bioassay results indicated that the alkyl chain length plays a key role in the neuritogenic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 26 publications
(22 reference statements)
0
16
0
Order By: Relevance
“…Priming PC-12 cells with MEK1/2 inhibitors (U0126 and PD98059) and PI3K inhibitor (LY294002) leads to inhibition of both the phosphorylation and activation of MEK/ERK1/2 and PI3K/AKT, respectively, and eventually diminishes the interrelated cellular processes [6567]. Liao et al (2012) [47] demonstrated that curcumin-induced neuritogenesis was mediated by MEK/ERK1/2 signaling pathway in PC-12 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Priming PC-12 cells with MEK1/2 inhibitors (U0126 and PD98059) and PI3K inhibitor (LY294002) leads to inhibition of both the phosphorylation and activation of MEK/ERK1/2 and PI3K/AKT, respectively, and eventually diminishes the interrelated cellular processes [6567]. Liao et al (2012) [47] demonstrated that curcumin-induced neuritogenesis was mediated by MEK/ERK1/2 signaling pathway in PC-12 cells.…”
Section: Discussionmentioning
confidence: 99%
“…DMEM and FBS were obtained from Gibco. MTT, Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), PI3K inhibitor LY294002 (purity ≥ 98% by HPLC), and 3-MA (purity ≥ 98% by TLC) were purchased from Sigma-Aldrich. LDH toxicology assay kit and ECL chemiluminescence kit were ordered from Wuhan Boster Biological Engineering Co., Ltd.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…The concentrations of drugs or agents were selected according to the related references. Cells were treated with emodin (10 µM) [13], 30 µM selective PI3K inhibitor LY294002 [30], or 5 mM 3-MA [17] for 1 h prior to 10 µM Aβ 25-35 exposure [31].…”
Section: Drug Administration For Pc12 Cellsmentioning
confidence: 99%
See 2 more Smart Citations